Clomipramine trial for treatment-resistant persistent genital arousal disorder: a case series. (2nd October 2017) - Yildirim, Ejder Akgun; Hacioglu Yildirim, Munevver; Carpar, Elif; Sarac, Irmak
Abstract: Introduction: Treatment of persistent genital arousal disorder (PGAD), as a chronic and disabling condition, implicates substantial compelling complexities. Methods: In this case series, seven women diagnosed with PGAD who were referred to the Sexual Dysfunction Unit of Psychotherapy Outpatient Clinic of Bakirkoy Research and Training Hospital for Psychiatry, Neurology, and Neurosurgery, Istanbul, Turkey between 2006 and 2009 were included. All patients were previously resistant to other antidepressants, antipsychotics and antiepileptics. The additional details of PGAD onset, frequency, type and duration of arousal, previous pharmacological interventions, and maximum and maintenance doses of clomipramine were recorded. Results: All patients achieved a substantial symptomatic improvement with clomipramine within the follow-up period of 2–9 years. Discussion: Based on our study results, we recommend clomipramine in combination with psychotherapy as the treatment of choice in PGAD and to be used before any invasive procedure such as electroconvulsive therapy (ECT) or surgery.